Tinjauan Kuat Tekan Dan Kuat Lentur Dinding Panel Dari Beton Ringan Dengan Perkuatan Diagonal Tulangan Bambu - Mahpudin, Hafid (2016)
In line with the development of the modern era, it needs to be balanced with the provision of alternative materials that are easy to obtain, easy maintenance, and less expensive than concrete that has been commonly used. In this case the panel with the reinforcement of the walls made of bamboo. In areas prone to earthquakes, the use of a brick wall unfavorable for earthquake-resistant houses. Wall panels are mild, thin, and strong is one material that is suitable for building houses that are earthquake resistant. Testing the compressive strength and flexure strength wall panel implemented by providing load on the surface of the wall panel, causing cracks and until it is destroyed. Bamboo apus is used because it has a fairly high tensile strength, low-cost and widely available in a variety of places. In this study aims to determine how much the compressive strength and flexure strength of open frame wall panels, wall panels without diagonal bracing bamboo, and wall panels with diagonal bracing bamboo. In this study bamboo apus is used as diagonal reinforcement with a diameter of 6 mm, 4 mm diameter steel, the distance between the steel frame and 5 cm at a distance of 8 cm on the diagonal and cement water factor (f.a.s) used 0,45. Concrete used type of mild concrete, in the form of concrete cylinders with a height of 30 cm, diameter 15 cm, 5 pieces and wall panels with a length of 100 cm, width 50, thickness 7 cm, as many as 20 pieces. Results from the study gained an average specific gravity of 1,710 gr/cm3 concrete cylinder, so that the concrete can be classified as mild, with the compressive strength by an average of 5,83 MPa. In testing the compressive strength of wall panels open frame, the average value of compressive strength of 0,644 MPa, while the compressive strength of wall panels without bracing diagonal bamboo, the average value of compressive strength of 2,094 MPa, and for compressive strength wall panels with bracing diagonal bamboo, the average value of compressive strength of 2,264 MPa. In the flexure strength testing panel wall without diagonal bracing bamboo, the average value of 2,755 MPa flexure strength, and flexure strength to panel walls with diagonal bracing bamboo, the average value of the flexure strength of 5,622 MPa. From these results, the compressive strength and flexure strength wall panels using diagonal bracing bamboo, has the greatest value.